Extracting edge flux intensity functions along part-elliptical 3-D cracks by the quasidual function method. (1st March 2020) - Schapira, Yaron; Yosibash, Zohar
Highlights: The quasidual function method was extended for extracting edge flux intensity function along part-elliptical singular edges. Very accurate EFIFs may be extracted from finite element (FE) solutions without the need of a refined FE mesh. Abstract: Part-elliptical crack fronts are common in real life, especially at free surfaces and at fastener holes. For such cases we herein extend the quasidual function method (QDFM) presented in Schapira and Yosibash (2019) to allow the extraction of edge flux intensity functions (EFIFs) from finite element solutions. We consider the Laplace operator, which provides a convenient framework for the extension of the QDFM to the elasticity operator. The QDFM post-processes the FE solution away from the singular edge. Numerical examples demonstrating the efficiency and accuracy of the proposed method are given for semi-elliptical and quarter-elliptical cracks.